Make the implicit explicit: Affirming right to vote in the Constitution would pre-empt the possibility of abuse by future govts - LEE, Jack Tsen-Ta (Institutional Knowledge at Singapore Management University, 2009)
There are sound reasons to set out explicitly and entrench in the Singapore Constitution the right to vote and key elements of the way elections are held. While a future government might not remove them entirely, it might derogate from them to the extent that they become unrecognizable.